Optimizing the Making of Karate Match Bracket with Tournament Bracket Seeding: Case Study of Inkanas West Java - Ferry Stephanus Suwita; Arif R Hakim (Peneliti.net, 2020)
Based on World Karate Federation regulations, organizers of both Karate and Kata Karate competitions must follow the World Karate Federation standards, including the use of new rules on panel point assessments for Kata Class and refer-change or double knockdown for Kumite Class. In Indonesia, the big competition has used the knockout system or refer-change. The biggest challenge for the organizers of the competition is to make the matchmaking tournament bracket balance with shorter time and less effort required. In one competition there are more than 100 class matches where from each class of matches must be provided a match bracket quickly and effectively. In general, the match bracket will be made after the athlete's data verification completed and technical meeting are held. Problems arise when athletes from the same contingent face off at the start of the match and this problem makes the bracket not balance. Several methods are used to create the match bracket, but the results are still less than optimal because the number of athletes from the same contingent that facing off each other at the beginning of the match is still high. With some experiment in applying the algorithm to the existing method, the Tournament Bracket Seeding is expected to overcome these problems effectively and efficiently. The output of the method is to decrease the percentage of athletes from the same contingent that not supposed to match at the beginning of the match